Genetics Influences Drug Consumption in Medication Overuse Headache, Not in Migraine: Evidence From Wolframin His611Arg Polymorphism Analysis - Di Lorenzo, Cherubino; Di Lorenzo, Giorgio; Coppola, Gianluca; Parisi, Vincenzo; Grieco, Gaetano S.; Santorelli, Filippo Maria; Pascale, Esterina; Pierelli, Francesco (Frontiers in Neurology, 2021)
Background. The Wolframin His611Arg polymorphism can influence drug consumption in psychiatric patients with impulsive addictive behavior. The aim of this cross-sectional study is to assess the prevalence of the Wolframin His611Arg polymorphism in MOH, a secondary headache belonging to the spectrum of addictive disorders, episodic migraine (EM), and healthy subjects (HS) and its influence on drug consumption. Methods. One-hundred and seventy-two EM, 107 MOH, and 83 HS were enrolled and genotyped for the Wolframin His611Arg polymorphism. Subjects were classified as homozygous for allele His (H/H subjects), homozygous for allele Arg (R/R subjects), and heterozygous (H/R subjects), regrouped as R/R and carriers of allele H (non-R/R), and matched for clinical data. Results. There were no differences in allelic distributions between the three groups (p=0.19). Drug consumption and other clinical characteristics were not influenced by the Wolframin His611Arg polymorphism (p=0.42; β=0.04) in the EM group. Among the MOH population, R/R subjects consumed more analgesics (p<0.0001; β=-0.38), particularly combination drugs (p=0.0001; d=2.32). Discussion. The Wolframin His611Arg polymorphism has similar prevalence between the MOH, EM, and HS groups. The presence of the R/R genotype does not influence symptomatic drug consumption in EM, whereas it determines an increased use of symptomatic drugs in the MOH group, in particular combination drugs (i.e., drugs containing psychoactive compounds). Conclusions. Our findings are consistent with the hypothesis that the Wolframin His611Arg polymorphism plays its effect only in the MOH population, influencing the impulsivity control underlying addictive behavior.